2010
DOI: 10.1177/145749691009900307
|View full text |Cite
|
Sign up to set email alerts
|

Tension-Free by Mesh-Plug Technique for Inguinal Hernia Repair in Elderly Patients

Abstract: Results: elderly patients had a mean age of 72.4 years (women 3.3%), while the mean age of younger patients was 48.7 years (women 5.7%). according to the asa score, patients aged ≥ 65 years were at significantly higher risk than the younger patients. spinal anesthesia was used most frequently in both groups. no significant differences were found in postoperative pain, mortality and recurrence. morbidity and hospital stay were significantly higher in patients aged ≥ 65 years.Conclusions: open hernia repair in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 25 publications
2
8
0
4
Order By: Relevance
“…About 20% of groin hernia repairs are done due to recurrences 22 . In a study by Pavlidis et al 14 , the recurrence rate after tension free technique for inguinal hernia repair was as low as 1.5%. Gianetta et al 23 reported a low recurrence rate of 1.8%, Liem et al 24 reported 6% recurrence, Champault et al 25 reported 2% recurrence and the MRC Laparoscopic Groin Hernia trial Group 26 and Amid et al 3 reported as low as 0% recurrence rate after open repair of groin hernia surgeries.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…About 20% of groin hernia repairs are done due to recurrences 22 . In a study by Pavlidis et al 14 , the recurrence rate after tension free technique for inguinal hernia repair was as low as 1.5%. Gianetta et al 23 reported a low recurrence rate of 1.8%, Liem et al 24 reported 6% recurrence, Champault et al 25 reported 2% recurrence and the MRC Laparoscopic Groin Hernia trial Group 26 and Amid et al 3 reported as low as 0% recurrence rate after open repair of groin hernia surgeries.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 94%
“…Elective repair of inguinal hernias is a low risk procedure which can be safely performed under general/ regional/local anesthesia with few complications and low mortality 13 , and should be performed soon after diagnosis is made and following adequate preparation even in the extreme elderly 14 . The incidence of inguinal herniation is higher in the elderly aged >65 years 15 and they also have concomitant medical problems which increase the risk of surgery, but even though morbidity in elderly is reported to be three times higher than in younger patients, age or comorbidity should not be a barrier to inguinal hernia repair 14 .…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Incidence rate of inguinal hernia is more in elderly patients above age of 65 years [11] who have medical diseases that increase surgical complications , morbidity in elderly patients was reported to be three folds more than in younger patients, despite that, age or comorbidity will not be contraindications to inguinal hernia repair [12].…”
Section: Discussionmentioning
confidence: 99%